Tipos documentais e sua relação com o processo decisório de uma empresa hospitalar da região de Bauru/SP - Nascimento, Natália Marinho do [UNESP] (2013)
Decisions are made constantly in organizational contexts; however, a wrong decision can bring undesirable consequences for organizations. In this sense, access to organic information becomes essential considering that decreases the uncertainties of managers in relation to decision making process. In this perspective, the identification of documental types from its production provides a consistent documental cycle, which will result in the recovery of information at the time requested by managers. Based on the above it was intended to verify what documental types recurrently used in the decision making process of a hospital company in the Bauru region, Sao Paulo State. For that, we applied the method 'Case Study' of Yin. We analyzed the information type that provided more security to the decision maker during the decision making. As a result, we elaborated a systematic documental organic types most used and most relevant to the decision-making process of the company, showing that when they are defined from the production of documents, the benefits for both the professional as archivist for the organization are significant.